Clinical Approach to Patients with Moderate-to-Severe Atopic Dermatitis: A Spanish Delphi Consensus - Jose J. Pereyra-Rodriguez; Esther S. Baldrich; Ricardo Ruiz-Villaverde; Eulalia B. Torres; Pablo de la C. Dobao; Ignasi F. Nart; Ángeles F. Menéndez; Ana Martin-Santiago; Javier M. Miquel; Juan F. Silvestre; Jose C. Armario-Hita (Medical Journals Sweden, 2023)
Despite emerging evidence and advances in the management of atopic dermatitis there a lack of consensus regarding the diagnostic criteria, therapeutic approach, method to assess severity, and patient follow-up for this condition. An expert consensus study was conducted to provide recommendations on the management of patients with moderate-to-severe atopic dermatitis. The study used Delphi-like methodology based on a literature review, a summary of the scientific evidence, and a 2-round survey. The agreement of 60 panellists on 21 statements was evaluated. Consensus was pre-defined as ≥ 80% agreement of all respondents. In the first round 6 statements reached consensus. Unanimous consensus was achieved regarding therapeutic goals and patient satisfaction (maintained in the long term and periodic goals reassessment recommended every 3-6 months). In the second round, half of the statements reached consensus, all related to patient follow-up, treatment goals, and atopic comorbidities. The statements that did not reach consensus were related to diagnosis (biomarkers, allergy, and food testing) and starting patients on conventional systemic treatment rather than advanced treatment. The study assessed expert opinion regarding a variety of topics related to the clinical approach to patients with moderate-to-severe atopic dermatitis, in order to provide guidance on the diagnosis and management of patients with atopic dermatitis.